KRITIK DALAM HUMOR MEME NURHADI – ALDO ERA DEMOKRASI DIGITAL - Irwanto Irwanto; Intan Leliana; Laurensia Retno H (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This paper attempts to highlight the meme of fictitious presidential and vice-presidential candidates Nurhadi - Aldo which consists of combining photos or images that are combined with the text. In addition, see how memes operate in political message traffic on Twitter's social media and its relationship with power and the accompanying social conditions. This meme delivered with humor contains criticism of social conditions and it gets attention to the community. This research looks at the discourse presented through memes on Twitter's social media.